BS EN 63171-7. Connectors for electrical and electronic equipment. Part 7. Detail specification for 4-way to 6-ways plus PE or FE (data/power) shielded, free and fixed circular connectors for balanced single-pair data transmission current-carrying capacity: mechanical mating information, pin assignment and additional requirements for type 7 (20th August 2021) - British Standards Institution,
No abstract available